2002
DOI: 10.1677/joe.0.1740045
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin-releasing peptide in the ewe: cDNA cloning, mRNA distribution and effects on prolactin secretion in vitro and in vivo

Abstract: RT-PCR followed by 5 -and 3 -rapid amplification of cDNA ends was used to clone and sequence ovine prolactin-releasing peptide (PrRP). The cDNA was characterised by short 5 -and 3 -untranslated regions and a GC-rich (71%) coding region. The nucleotide and deduced amino acid sequences for the coding region showed 95·6 and 94·9% identity with bovine PrRP but the amino acid sequence of PrRP31 was conserved between these species. Northern blot analysis and RT-PCR showed that, as in the rat, the peptide was more ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 21 publications
(38 reference statements)
0
31
2
Order By: Relevance
“…result, since the amino acid sequence of PrRP is identical between cattle and sheep [32]. The use of OVX ewes also does not explain this result, since it has been demonstrated that the cortisol response to stress is higher in the OVX ewe than in the estradiol-treated OVX ewe [33].…”
Section: Central Npb Activates the Hpa Axis In Sheepmentioning
confidence: 94%
See 1 more Smart Citation
“…result, since the amino acid sequence of PrRP is identical between cattle and sheep [32]. The use of OVX ewes also does not explain this result, since it has been demonstrated that the cortisol response to stress is higher in the OVX ewe than in the estradiol-treated OVX ewe [33].…”
Section: Central Npb Activates the Hpa Axis In Sheepmentioning
confidence: 94%
“…Consequently, the present result suggests that central PrRP does not participate in control of the HPA axis in sheep. Curlewis et al [32] found that PrRP mRNA is abundantly expressed in the ventromedial hypothalamus and brainstem of sheep. However, they also failed to observe any change in the plasma prolactin concentration after an icv injection of 50 nmol of PrRP in sheep [32].…”
mentioning
confidence: 99%
“…Maintenance of increased lactotroph activity during lactation seems to require additional factor(s) enhancing prolactin synthesis and release. Recently, some hypothalamic compounds are thought to play the role of prolactin-releasing factor (PRF; Maruyama et al 1999, Curlewis et al 2002, Samson et al 2003 and amongst them, salsolinol that paradoxically may be produced by the inhibitory NEDA system (Mravec 2006).…”
Section: Introductionmentioning
confidence: 99%
“…TRH receptors have been identified on type II and type III of lactotrophs but not any labelling was evident on type I. Other studies have revealed that the stimulatory influence of PrRPs-31 on PRL release in rats is rather low compared to TRH or VIP (Samson et al, 1998;Curlewis et al, 2002;Swinnen et al, 2005;Christian et al, 2007).…”
Section: Factors Stimulating Prolactin Releasementioning
confidence: 88%
“…The PrRPs-31 has no stimulatory effect on PRL release in sheep (Curlewis et al, 2002), but it is essential for secretion of this hormone in teleost fish (Sakamoto et al, 2003). Chicken PrRPs-31/32 increases plasma PRL concentration in chicks when administered peripherally whereas infused centrally decreases PRL release, suggesting that in these animals PrRPs-31/32 has distinct effect on PRL secretion between tissue (Tachibana et al, 2011).…”
Section: Factors Stimulating Prolactin Releasementioning
confidence: 97%